2007
DOI: 10.2320/matertrans.48.158
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ZrCuAlNi Metallic Glassy Matrix Composite Containing ZrO<SUB>2</SUB> Particles by Spark Plasma Sintering Process

Abstract: Using a mixed powder of argon gas-atomized Zr 55 Cu 30 Al 10 Ni 5 metallic glassy alloy powder blended with 10 vol% ZrO 2 powder, Zr 55 Cu 30 Al 10 Ni 5 bulk metallic glassy matrix composite was fabricated by a spark plasma sintering process. The structure, thermal stability and mechanical properties of the sintered bulk metallic glassy matrix composite were investigated. The ZrO 2 particles were homogeneously dispersed in the Zr 55 Cu 30 Al 10 Ni 5 glassy matrix. No crystallization of the glassy matrix occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…2. We have demonstrated in our previous studies that the crystallization of Zr-and Ni-based BMGs and their composites was avoided upon the SPS process [14,17,18,30,31]. The significant viscous flow deformation under high pressure at a proper temperature and a certain holding time promotes effective diffusion from one to another glassy phase, and results in continuous connection between the glassy phases (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…2. We have demonstrated in our previous studies that the crystallization of Zr-and Ni-based BMGs and their composites was avoided upon the SPS process [14,17,18,30,31]. The significant viscous flow deformation under high pressure at a proper temperature and a certain holding time promotes effective diffusion from one to another glassy phase, and results in continuous connection between the glassy phases (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The disappointingly poor plasticity limits the extensive practical applications of BMGs. In order to overcome this problem, a method which is to introduce nano-or micro-scale crystalline phases into the metallic glassy matrix leading to the formation of multiple shear bands and an enhanced plasticity has been proposed [6][7][8][9][10][11][12][13][14]. Some attempts have been carried out: such as inclusion of nanoscale compound particles dispersed in the glassy matrix via thermal treatment [15], adding particles or fibers during casting or consolidation process [9][10][11][12], and in situ formed ductile phase precipitates [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the SPS process is a type of compression sintering technique which is similar to hot-pressing (HP) sintering process, so that the sintered specimens with the largesize and complicated shape can be easily produced [16,17]. It has been reported that the Zr-based [4,5,15], Cu-based [18,19], Fe-based [20,21], and Ni-based [3,22] BMGs were fabricated by the SPS process. Using the mixed powders of gas-atomized metallic glassy alloy powder blended with crystalline (metal or ceramic) powders, we fabricated large-size bulk GAC specimens by the SPS process.…”
Section: Introductionmentioning
confidence: 98%